EXPLORATION AND SCREENING FOR ENDOPHYTIC MICROBES OF MAIZE PLANT ROOT AGAINST FUSARIUM VERTICILLIOIDES - Rahmat Jahuddin; Jamila .; Awaluddin .; Suriani . (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2018)
Exploration and Screening for Endophytic Microbes of Maize Plant Root against Fusarium verticillioides. Fusarium verticilloides is an important pathogen of maize which can attack cob and stem causing ear rot and stalk rot disease. Fusarium ear rot disease needs to get a serious attention because the mycotoxins produced by this pathogen very harmful for consumers. The aim of this study was to screen maize roots endophytic microbes as antagonist to F. verticilloides. Endophytes microbial exploration is done by taking samples of local roots of South Sulawesi and hybrid maizes in Soppeng Regency then isolated in Biological Laboratory of Islamic University of Makassar. The endophytes were then tested their effectiveness on inhibiting growth of mycelia pathogenic F. verticilloides by using dual culture method and tested the suppressing ability of F. verticilloides on maize seed and their influence on seed sprout length. The results showed that there were 8 endophytic microbes consisting of 4 isolates of the fungus group namely HS-01, HS-02, HS-04, LS-01 and 4 isolates from bacterial group namely HS-03, LS-02, LS-03, LS-04. While the results of microbial effectiveness testing on pathogenic F. verticilloides showed that HS-04 has the highest percentage of inhibition followed by isolate HS-01, HS-02 and LS-02. HS-04 isolate also showed the ability to suppress F. verticilloides attacks on corn seeds at 77.78%. The highest seed sprout length was shown in LS-02 isolate application about 10.57 cm. Thus it can be concluded that there were 3 potentially endophytic microbes to control the F. verticilloides namely HS-04, HS-01 and LS-02. The ability to stimulate plant growth became one of considerations to select these three microbes.